Introduction: The Forgotten Subject in Communication Studies - Gentzel, Peter; Krotz, Friedrich; Wimmer, Jeffrey; Winter, Rainer (The Forgotten Subject, 2023)
The volume focuses on the question of the transforming relationship between subject, communication and society, in which – according to our thesis – the currently rapid change of media plays a central role. The mediatization approach is recommended as an entry point into this complex question for several reasons, because it represents an analytically consistent perspective that brings together communicative and medial processes of change with social and cultural ones. From this perspective, subjects emerge on the basis of communicative actions, practices and habits and the processing of the experience associated with them, all of which are in turn closely linked to social contexts and processes.<br